Household indebtedness and financial literacy in Turkey - Daşdöğen, Sezgin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This thesis aims to understand which factors affect households’ decision to enter the credit market and the amount of debt they obtain, using data from the Credit Card Consumer Survey conducted in 2009 on 2576 credit card users across Turkey. Since this data presents information about different subcategories of debt, namely formal, informal and credit card debt, we examine whether different debt types have similar or different determinants. The possible factors that can affect formal, informal, credit card and total debt are investigated under five main categories: financial literacy, life cycles, economic situation, ability to get credit, and demographics. Financial literacy is divided into three components: financial inclusion, financial knowledge and financial behavior. We show that, more than financial information, it seems that people’s financial behavior and attitudes make a difference in indebtedness levels and smart borrowing. Education to improve behavior (on money management, for example) and regulations on the usage of credit cards (to prevent imprudent behavior, for example) may be relevant policy tools to be employed. This thesis can serve as a useful beginning point for the rapidly growing Turkish credit market and it can contribute to the designing of various solutions for the rising indebtedness problem for different household profiles.
Keywords: Debt relief -- Turkey.; Households -- Turkey.; Finance, Personal.